KORELASI LAMA HEMODIALISIS DENGAN PENINGKATAN INTERDIALYTIC WEIGHT GAIN (IDWG) PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RSUD dr. LOEKMONOHADI KUDUS - Devi Setya Putri; Luluk Cahyanti; Eka Vira (Poltekkes Kemenkes Aceh, 2023)
Hemodialysis is a procedure that can improve the quality of life for patients with chronic kidney disease. The longer undergoing hemodialysis it will be increasingly exposed to complications from hemodialysis. The complication that often occurs is an increase in Interdialytic Weight Gain (IDWG). The purpose of this study is to correlation longer undergoing hemodialysis and increase in Interdialytic Weight Gain (IDWG). This type of research is descriptive correlation. The sample in this study were 51 respondents who underwent hemodialysis in RSUD dr. Loekmono Hadi Kudus. This study uses a purposive sampling technique. Bivariate analysis uses rank spearmen. The average respondent underwent hemodialysis for 19.92 months and the average IDWG increase in respondents was 1.995 kg. Bivariate results show that p value is 0.004 (α = 0.05). There is a relationship between long-term in hemodialysis and the increase in IDWG in patients with chronic kidney disease on hemodialysis patients at dr. Loekmono Hadi Hospital Kudus.